The Tacit Dimension : Architecture Knowledge and Scientific Research - Schrijver, Lara (Book collections on Project MUSE., 2021)
Within architecture, tacit knowledge plays a substantial role both within the design process and its reception. This book explores the tacit dimension of architecture in its aesthetic, material, cultural, design-based, and reflexive understanding of what we build. Much of architecture's knowledge resides beneath the surface, in nonverbal instruments such as drawings and models that articulate the spatial imagination of the design process. Tacit knowledge, described in 1966 by Michael Polanyi as what we "can know but cannot tell", often denotes knowledge that escapes quantifiable dimensions of research. Beginning in the studio, where students are guided into becoming architects, the book follows a path through the tacit knowledge present in models, materials, conceptual structures, and the design process, revealing how the tacit dimension leads to craftsmanship and the situated knowledge of architecture-in-the-world. Awareness of the tacit dimension helps to understand the many facets of the spaces we inhabit, from the ideas of the architect to the more hidden assumptions of our cultures.